Profile of appendicitis patient: epidemiology, clinical, and laboratories evaluation in rural-urban area - Heriyanto, Moch Junaidy; Ratnaningsih, Tri; Fatimah, Bunga; Putri, Rona Hafida Heriyanto; Nisa, Afifah Khairu (International Journal of Public Health Science (IJPHS), 2023)
Appendicitis is one of the most common abdominal inflammations in daily emergency cases. The diagnosis of appendicitis is often delayed because the symptoms resemble other abdominal emergencies. The present research aimed to describe the clinical and epidemiological profile of acute appendicitis patients. The research design is a cohort retrospective study employing appendicitis patients' medical record data at PKU Muhammadiyah Hospital from January 1, 2016, to December 31, 2020. The variables obtained through the patient records were age, gender, domicile location, vital signs, physical examination, blood laboratory, ultrasound, histopathology, postoperative diagnosis, the incidence of peritonitis, and length of stay. The median age value in patients with appendicitis was 27 years (0-95), and the largest group was young adults (19-44 years). Abdominal pain was found in almost all research subjects. The median of leukocytes was 10.1 (3.32-65.80)×106/ml and the neutrophil-lymphocyte ratio (NLR) was 3.52 (0.47-30.57)/μl. The median percentage of the neutrophil count was 70.7 (27.90-94.81). The final diagnosis of complicated appendicitis was more than uncomplicated appendicitis (51.2% vs. 48.8%). We conclude that several detailed parameters, such as the location of abdominal pain, leukocyte count, and NLR can help the physician diagnose appendicitis and guide surgeons in deciding the type of surgery.